Pentahelix Collaboration in Achieving Disaster Preparedness through Resilient Villages: A Systematic Literature Review - Dwi Yunanto Hermawan; Evi Widowati; Sofwan Indarjo; Efa Nugroho; Annisa Novanda Maharani Utami (Jurnal Kesehatan Masyarakat, 2025)
Pentahelix is one of the disaster preparedness approaches. This study aimed to provide an overview of the roles of each component in pentahelix collaboration occurring in several countries, thereby enhancing the effectiveness of disaster preparedness. Indonesia is the country with the second-highest disaster risk in the world, with a total of 3,472 disasters occurring in 2024.. Pentahelix collaboration has not been optimal, and disaster preparedness has not been achieved. This systematic literature review was conducted in accordance with PRISMA guidelines, compiling relevant studies from databases including PubMed, ScienceDirect, and Scopus. The literature search was carried out between April and June 2024 using specific keywords. The search yielded a total of 3.848 articles across the selected databases. Of these, 2.384 articles were obtained from Scopus, 1.277 from Science Direct, and 187 from PubMed. After the screening process, 13 relevant articles were identified for further review. Conclusion: the Government, private sector, community, academics, and media play crucial roles in disaster preparedness effectiveness. Overall, the success of disaster preparedness depends on strong cooperation and coordination among all stakeholders. Strong coordination and close collaboration among all stakeholders through Penthahelix collaboration are crucial to minimize the impact of disasters and accelerate the recovery of critical infrastructure.